Intermolecular Regio‐ and Stereoselective Hetero‐[5+2] Cycloaddition of Oxidopyrylium Ylides and Cyclic Imines. (13th December 2018) - Zhao, Changgui; Glazier, Daniel A.; Yang, Daoshan; Yin, Dan; Guzei, IIia A.; Aristov, Michael M.; Liu, Peng; Tang, Weiping
Abstract: We have developed the first intermolecular hetero‐[5+2] cycloaddition reaction between oxidopyrylium ylides and cyclic imines with excellent control of regio‐ and stereoselectivity. Surprisingly, divergent stereochemistry was observed depending on the substitution pattern of the oxidopyrylium ylide. This new reaction provides quick access to highly substituted nitrogen‐containing seven‐membered rings—azepanes. Notably, a broad range of oxidopyrylium ylides and cyclic imines participate in this novel hetero‐[5+2] cycloaddition reaction and the cycloadducts can be readily transformed into the core skeletons of bioactive natural products. DFT calculations revealed that the cycloaddition proceeds through a stepwise pathway and the imine nitrogen atom serves as the nucleophile to initiate the cycloaddition.